Low Energy Electron- and Ion-Induced Surface Reactions of Fe(CO)5 Thin Films - Bilgilisoy, Elif; Thorman, Rachel M; Barclay, Michael S; Marbach, Hubertus; Fairbrother, D. Howard (Journal of physical chemistry. C, 2021)
Using in situ X-ray photoelectron spectroscopy (XPS), the effects of low energy (500 eV) electrons and low energy (1200 eV) Ar+ ions on thin films of Fe(CO)5, a prototypical organometallic precursor, have been investigated. These studies were motivated by the important role that these surface reactions play in the charged-particle-induced deposition of nanostructures. XPS data from the C(1s) and O(1s) regions were used to construct kinetic models to describe the effects of electron and ion irradiation, both of which occurred through a sequence of two sequential surface reactions, although the details of each step differ. During electron irradiation, precursor molecules initially decompose as a result of electronic excitation, resulting in desorption of approximately 50% of the CO ligands and partial decarbonylation within the Fe(CO)5 film. In the second step, the partially decarbonylated intermediates undergo a much slower electron-stimulated CO decomposition process to produce iron oxides encased in a graphitic film. Fe2(CO)9 and Fe3(CO)12 reacted similarly to Fe(CO)5, but the initial rate of decomposition was an order of magnitude higher. During Ar+ bombardment, Fe(CO)5 molecules decompose as a consequence of energy transfer from the incident ions, causing complete fragmentation of the precursor and desorption of ≈80% of the CO molecules. The remaining 20% undergo CO bond cleavage, forming adsorbed carbon and volatile oxygen species. In the second step of the reaction, the residual iron and carbon atoms are subject to Ar+ ion sputtering. The implications of these reactions for focused ion beam-induced deposition (FIBID) and focused electron beam-induced deposition (FEBID) from Fe(CO)5 are also discussed.